1983
DOI: 10.1007/bf02666588
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of soybean oil as a diesel fuel extender: Endurance tests

Abstract: Engine performance and crankcase lubricant viscosity were followed with 1:2 and 1:1 fuel mixtures of degummed soybean oil in No. 2 diesel fuel in tests with a John Deere 6-cylinder, 404 cubic in. displacement, direct-injection, turbocharged engine for a total of 600 running hours. A crankcase oil contamination problem resulting in an unacceptable thickening and a potential for gelling did exist with a 50/50 blend or a greater concentration of soybean oil, but it did not occur with the 1:2 blend. The data accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…The authors concluded that fatty oil methyl esters may show promise as an alternative diesel fuel. Another paper cited similar studies where serious injector fouling and crankcase oil thickening problems had occurred when vegetable oils were used as diesel fuels 45 .…”
Section: Early Workmentioning
confidence: 98%
“…The authors concluded that fatty oil methyl esters may show promise as an alternative diesel fuel. Another paper cited similar studies where serious injector fouling and crankcase oil thickening problems had occurred when vegetable oils were used as diesel fuels 45 .…”
Section: Early Workmentioning
confidence: 98%
“…The irst approach consisted on directly using vegetable oils without any chemical transformation as direct fuel. Thus, soybean oil [35], sunlower oil [36], canola oil [37] or rapeseed oil [38] have been studied. However, the direct use of vegetable oils or the use of blends with traditional petroleum-based diesel has not been considered a suitable solution due to the high viscosity, the gum formation due to oxidation processes and the deposition of carbon on piston and head of the engines [39].…”
Section: Transesteriication Of Grape Seed Oil For Biodiesel Productionmentioning
confidence: 99%
“…2 diesel fuel in the ratios of 1:2 and 1:1 were tested for engine performance and crankcase lubricant viscosity in a John Deere 6-cylinder, 6.6 L displacement, direct-injection, turbocharged engine for a total of 600 h (Adams et al, 1983). The lubricating oil thickening and potential gelling existed with the 1:1 blend, but it did not occur with the 1:2 blend.…”
Section: Direct Use and Blendingmentioning
confidence: 99%